Trend of mobile communication market pattern under the reform of industry co-competition - Su DIAO; Cheng JIANG (Dianxin kexue)
In October 2019, with the nationwide implementation of mobile number portability, MIIT and SASAC strengthened industry competition supervision and initiated the industry co-competition of the three major telecom operators in China.The short-term development trend of China mobile communications market was predicted by utilizing Markov chain model to analyze the changes in the market share of mobile communication market, and the state transition probability matrixes before and after the change of the industry’s competitive environment caused by regulatory policies were innovatively compared.The study shows that the impact of industry co-competition reform is greater the nationwide implementation of MNP, the probability of mobile users to lock-in has increased.According to the prediction of the state transition probability matrix after industry co-competition, China Telecom’s mobile market share will increase, while China Mobile and China Unicom Mobile’s market share will decline in the short and medium term.However, China Mobile will continue to maintain its dominant position.To accelerate 5G high-quality development and open up a new pattern in the mobile communication market, the industry co-competition environment needs to be further optimized to strengthen regulatory policy, 5Gco-construction, and operation management.